Karakter Bima Sebagai Sumber Inspirasi dalam Karya Seni Grafis - Bagaskoro Ardhi; Nooryan Bahari; Sigit Purnomo Adi1 (Institut Seni Indonesia Yogyakarta, 2018)
The resulting graphic artwork was inspired by the Bima puppet figure who was dashing, muscular, athletic, honest, brave, never giving up, warlord, and accomplished knight. Bima’s characters and attributes are then poured in this graphic art. This work was created using a high-speed/print technique that has a unique shading effect, such as a texture effect because it goes through the printing process many times. The basic principles of art include unity, balance, harmony, proportion (proportion), and emphasis (domination) used as a theoretical framework. The author utilizes reproductive works in the form of photos of print media and from the internet to be explored. There are 14 works produced from the exploration. Karya seni grafis yang dihasilkan terinspirasi dari tokoh wayang Bima yang gagah, kekar, atletis, jujur, pemberani, pantang menyerah, panglima perang, dan ksatria ulung. Karakter dan atribut Bima itulah yang kemudian dituangkan dalam karya seni grafis ini. Karya ini diciptakan dengan menggunakan teknik cukil tinggi/relief print yang memiliki efek cukilan yang unik, seperti efek tekstur karena melalui proses cetak berkali-kali. Prinsip dasar seni rupa antara lain kesatuan (unity), keseimbangan (balance), keselarasan (ritme), perbandingan (proportion), dan penekanan (domination) dipakai sebagai kerangka teori. Penulis memanfaatkan karya reproduksi berupa foto media cetak maupun dari internet untuk dieksplorasi. Ada 14 karya yang dihasilkan dari eksplorasi tersebut.